Sex‐Modified Effects of Depression, Low Back Pain, and Comorbidities on Pain After Total Knee Arthroplasty for Osteoarthritis. Issue 8 (3rd July 2020) - Perruccio, Anthony V.; Fitzpatrick, Jessica; Power, J. Denise; Gandhi, Rajiv; Rampersaud, Y. Raja; Mahomed, Nizar N.; Davey, J. Roderick; Syed, Khalid; Veillette, Christian; Badley, Elizabeth M.
Abstract : Objective: The influence of sex on post–total knee arthroplasty (TKA) outcomes has been variable in the literature. Though sex is often reported as an averaged effect, we undertook this study to investigate whether sex modified the influence of presurgery characteristics on post‐TKA knee pain. Methods: This was a prospective study with data derived from 477 TKA osteoarthritis patients (279 women, 198 men). Questionnaires were completed presurgery and at 3 months postsurgery. The association between 3‐month post‐TKA knee pain and presurgery covariates (body mass index, comorbidity count, symptomatic joint count, low back pain, knee pain, and depressive symptoms) was assessed by linear regression. Sex‐specific effects were evaluated using interactions. Results: Women had significantly worse presurgery knee pain, joint count, and depressive symptoms, and worse postsurgery knee pain, than men. With simple covariate adjustment, no sex effect on pain was found. However, sex was found to moderate the effects of comorbidities (worse for women [ P = 0.013]), presence of low back pain (worse for men [ P = 0.003]), and depressive symptoms (worse for men [ P < 0.001]) on postsurgery pain. Worse presurgery pain was associated with worse postsurgery pain similarly for women and men. Conclusion: The influence of some patient factors on early post‐TKA pain cannot be assumed to be the same for women and men; average effects may mask underlying associations. Results suggest a need to consider sex differences in understanding TKA outcomes, which may have important implications for prognostic tool development in TKA.